Parálisis, parloteo y performance en Potestad de Eduardo Pavlovsky - Meléndez, Priscilla (Latin American Theatre Review, 2016)
From the perspective of time and space, this essay analyzes the way in which Eduardo Pavlovsky’s Potestad (1985) transforms the outrageous speeches of the protagonist and his excessive bodily movements into signs of physical, psychological, and moral paralysis. Such an approach serves to reveal the dialogic, proxemic, historical, and temporal schemes of the play. The author examines the dialogue and tension established between the protagonist’s harangues, his obsession with the positions of the characters, and his closely timed bodily activity and the relation between these discourses and an audience forced to harmonize the contradictions between what it hears and sees and the places occupied by people and objects. Through the theatricalization of silence and paralysis, Potestad questions the traditional notion of theatre as dialogue and action, thus creating an ambiance of ambiguity, trickery, and emptiness.